Reinterpretation of the Meaning of Violence Against Women (Study of Contextual Studies and Women's Protection in Hadith) - Sundayani, Neneng Sri; Yusuf, Muhammad Waliyuddin; Masruhan, Masruhan; Musyafaah, Nurlailatul (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2026)
Abstract: Domestic violence, particularly involving wife-beating (daraba), has long been a controversial topic in Islamic religious studies and gender issues. A direct understanding of the related hadith is often used as an excuse for committing acts of violence against women within the household. This study aims to re-explore hadiths on domestic violence using a contextual interpretation approach, in order to find a more just meaning, appropriate to the current context, and in line with the principle of protecting women's rights. The method used in this study is qualitative, with a textual and hermeneutic analysis approach to classical hadith sources, contextual interpretations, and literature on human rights and gender issues. The results show that contextual interpretations not only interpret hadiths from the perspective of their literal meanings but also consider the historical context and universal moral values in Islam. The hadith on wife-beating is understood not as a command to commit violence, but as an effort to limit the practice of violence that already existed in patriarchal Arab society at that time. The contextual interpretation approach emphasizes the importance of compassion, deliberation, and justice as the basis for the relationship between husband and wife. Thus, reinterpreting the hadith through contextual interpretation is very important to strengthen protection for women and to build a harmonious household in accordance with the principles of maqāṣid al-syarī'ah.Keywords: Hadith, Domestic Violence, Protection of Women. Abstrak : Kekerasan dalam rumah tangga, terutama yang melibatkan pemukulan istri (daraba), sudah lama menjadi topik yang dipermasalahkan dalam studi agama Islam dan isu gender. Pemahaman langsung terhadap hadis yang berkaitan sering digunakan sebagai alasan untuk melakukan tindakan kekerasan terhadap perempuan di dalam rumah tangga. Penelitian ini bertujuan untuk mengeksplorasi kembali hadis-hadis tentang kekerasan dalam rumah tangga dengan pendekatan tafsir yang kontekstual, agar dapat menemukan makna yang lebih adil, sesuai dengan konteks masa kini, dan selaras dengan prinsip melindungi hak perempuan. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan analisis teks dan hermeneutik terhadap sumber-sumber hadis klasik, tafsir kontekstual, serta literatur mengenai hak asasi manusia dan isu gender. Hasil penelitian menunjukkan bahwa tafsir kontekstual tidak hanya menafsirkan hadis dari sudut makna kata, tetapi juga mempertimbangkan konteks sejarah dan nilai-nilai moral universal dalam Islam. Hadis tentang pemukulan istri dipahami bukan sebagai perintah untuk melakukan kekerasan, tetapi sebagai upaya membatasi praktik kekerasan yang sudah ada di masyarakat Arab yang berpatriarki pada masa itu. Pendekatan tafsir kontekstual menekankan pentingnya nilai kasih sayang, musyawarah, dan keadilan sebagai dasar dalam hubungan antara suami dan istri. Dengan demikian, interpretasi ulang hadis melalui tafsir kontekstual sangat penting untuk memperkuat perlindungan terhadap perempuan dan dalam membangun rumah tangga yang harmonis sesuai dengan prinsip maqāṣid al-syarī‘ah.Kata kunci: Hadis, Kekerasan dalam Rumah Tangga, Perlindungan Perempuan.